Complicaciones agudas de la diabetes en los usuarios del servicio de medicina interna del Hospital General Isidro Ayora de Loja, junio 2014-junio 2015. - Cabrera Rojas, Christian Iván (2017)
Diabetes is a chronic disease that occurs when the pancreas does not produce enough insulin or when the body does not effectively use the insulin it produces. The present study has as general objective to determine the frequency of acute complications in patients with DM2 diagnosis, who entered the service of internal medicine in the Hospital Isidro Ayora de Loja, in the period June 2014 - June 2015, specific objectives; To identify cases of diabetic ketoacidosis, hyperglycemic hyperosmolar state and hypoglycemia, besides classification by gender and age, the study is descriptive retrospective. We studied a universe of 376 patients diagnosed with T2DM who were hospitalized and a convenience sample of 75 patients who presented with one of the acute complications of T2DM. . The data were collected in a collection sheet prepared by the author, obtaining the following: Of a universe of 376 patients who were hospitalized in the internal medicine service, with a diagnosis of DM2, 75 cases presented some of the acute complications, 57.3 % Were women and 42.7% were men, 38.7% had diabetic ketoacidosis, 9.4% presented hyperglycemic hyperosmolar state, 52% presented hypoglycemia, the most frequent presentation age was between 50 and 59 years, with 28 % Of cases, and the less frequent age was between 80 and 89 years of age. Key words: type 2 diabetes mellitus, diabetic ketoacidosis, hyperglycemic hyperosmolar state, hypoglycemia.